2021
DOI: 10.5194/esd-12-233-2021
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical systems characterization of atmospheric jet regimes

Abstract: Abstract. Atmospheric jet streams are typically separated into primarily “eddy-driven” (or polar-front) jets and primarily “thermally driven” (or subtropical) jets. Some regions also display “merged” jets, resulting from the (quasi-)collocation of the regions of eddy generation with the subtropical jet. The different locations and driving mechanisms of these jets arise from very different underlying mechanisms and result in very different jet characteristics. Here, we link the current understanding of dynamica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…These metrics are related to the intrinsic predictability of the atmosphere and therefore to the stability (here in the context of atmospheric variability) of the flow: a highly persistent (low θ ), low‐dimensional (low d ) state will be more stable than a low‐persistence (high θ ), high‐dimensional (high d ) one (Messori et al., 2017). This approach has been applied to various atmospheric fields (e.g., Faranda et al., 2019a; Messori et al., 2021). Indeed, it has been shown that d and θ can offer a dynamical characterization of synoptic systems over several geographical regions (Faranda, Alvarez‐Castro, et al., 2017; Hochman et al., 2019; Hochman, Alpert, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These metrics are related to the intrinsic predictability of the atmosphere and therefore to the stability (here in the context of atmospheric variability) of the flow: a highly persistent (low θ ), low‐dimensional (low d ) state will be more stable than a low‐persistence (high θ ), high‐dimensional (high d ) one (Messori et al., 2017). This approach has been applied to various atmospheric fields (e.g., Faranda et al., 2019a; Messori et al., 2021). Indeed, it has been shown that d and θ can offer a dynamical characterization of synoptic systems over several geographical regions (Faranda, Alvarez‐Castro, et al., 2017; Hochman et al., 2019; Hochman, Alpert, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of individual states together with the local attractor dimension can be used as a dynamical proxy of the general circulation. This approach has already successfully been applied to dynamical features of the atmosphere (Faranda et al, 2017;Messori et al, 2021)), but never, to the best of our knowledge, to thermodynamic features.…”
Section: Discussionmentioning
confidence: 99%
“…Here, u and σ are parameters of the distribution which depend on the chosen ζ x , while ϑ is the extremal index: the standard measure of clustering in extreme value theory (Moloney et al, 2019). We estimate the latter using the Süveges maximum likelihood estimator (Süveges, 2007).…”
Section: Theoretical Underpinnings Of the Dynamical Systems Frameworkmentioning
confidence: 99%
“…The code to compute the three dynamical systems indicators used in this study is made freely available through the cloud storage of the Centre National de la Recherche Scientifique (CNRS) under a CC BY-NC 3.0 license: https://mycore. core-cloud.net/index.php/s/pLJw5XSYhe2ZmnZ (Faranda, 2021).…”
Section: Appendix A: Additional Figuresmentioning
confidence: 99%